2011
DOI: 10.7763/ijcte.2011.v3.355
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Outbreak Prediction: A Least Squares Support Vector Machines Approach

Abstract: Malaysia. Her research interest is broadly in data analysis and management for large scale computing. This includes data mining (discovering patterns of interest from data), data warehousing, information retrieval and software reuse. Zuriani Mustaffa obtained her B. Sc (Hons) in Computer Science (Software Engineering) from University Teknologi Malaysia in 2003. She just completed her M. Sc (Information Technology) from University Utara Malaysia. Her research interests are machine learning and artificial intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 12 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Data scaling refers to the method used to normalize the range of features or independent variables of a data mining model. This approach can ensure that data are not overwhelmed by each other in terms of distance measures [ 33 ]. We used a standardization technique ( Eq 8 ) to rescale both the training and testing data: where x ′ is a standardized value, x is an original value, and mean and stddev are a median and a standard deviation value of each feature ( f ), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data scaling refers to the method used to normalize the range of features or independent variables of a data mining model. This approach can ensure that data are not overwhelmed by each other in terms of distance measures [ 33 ]. We used a standardization technique ( Eq 8 ) to rescale both the training and testing data: where x ′ is a standardized value, x is an original value, and mean and stddev are a median and a standard deviation value of each feature ( f ), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The SVM can solve several problems of classification techniques such as the overfitting problem and the curse of dimensionality. The SVM has been proven to provide more solutions to boundaries compared to the neural network (NN) and can solve local minimum problems found in the NN [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yusof and Mustaffa [21] observed that neural network (NN) and least square SVM (LS-SVM) require simpler calculations and less complexity in training than the regular SVM. Their comparison on applying the NN and LS-SVM to data collected from five Malaysian cities showed that the LS-SVM outperformed the NN in accuracy and runtime.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the relation between weather conditions and the proliferation of the dengue vector mosquito, statistical and machine-learning models can be used for forecasting the number of dengue cases based on weather conditions [11,12,21]. The detection of such outbreaks in advance would give to public health agencies time for dealing with the high number of cases and even decrease them.…”
Section: Introductionmentioning
confidence: 99%
“…model [27,28] which only has the objective of shortterm forecasting of the ongoing outbreak or model early warning system [16,29,30] which aims to be a descriptive analysis of the region that has the potential to endemic but no regional cluster patterns in each area are predicted. The research that has been carried out is still limited to descriptive analysis in the form of a numerical table of each variable characteristic.…”
Section: Related Workmentioning
confidence: 99%